THE REQUIREMENTS OF THE ENEM ESSAY IN CONTRAST WITH CONTEMPORARY SCHOLARLY WRITING - Fabíola Silva de Faria, Vanessa; GRANDI, PRISCILLA (Revista de Letras Norte@mentos, 2025)
This study analyzed the use of connectors in four different text genres: a journalistic oral interview, an opinion article, a contemporary literary text, and an essay written by a high school student for the National High School Exam (ENEM). The main goal was to examine the usage patterns of these connectors, comparing them with the standards set by the National Institute of Educational Studies and Research Anísio Teixeira (INEP) regarding connectors in argumentative-essay texts. Through our analysis, it became evident that in terms of the variety of connectors, the more formal texts—expected to employ a wide range of connectors—frequently showed repeated use of the same ones throughout the text. Therefore, this finding encourages a reassessment of ENEM’s guidelines for essay writing, which emphasize the importance of diversified connectors as a demonstration of proficiency in multiple textual cohesion mechanisms, ruled by normative grammar.